Humeral Head Osteochondral Allograft Reconstruction for Chronic Locked Posterior Glenohumeral Dislocation With Large Reverse Hill-Sachs Defect - Emma E. Johnson BA; Michael Campbell MD; Steven B. Cohen MD (SAGE Publishing, 2022)
Background: Locked posterior glenohumeral dislocations are a rare but often missed injury when it occurs. In these dislocations, patients may have a reverse Hill-Sachs lesion, which are associated with high rates of recurrent posterior glenohumeral instability. Open reduction with allograft reconstruction to reconstruct the defect can be used to treat chronic locked posterior glenohumeral dislocations. Indications: Osteochondral allograft reconstruction is indicated when patients have a large defect affecting less than 50% of the articular surface and if the humeral head has been dislocated for less than 6 months. Technique Description: With the patient in beach chair position, exposure is obtained through deltopectoral approach. An open reduction is performed, and the defect is debrided down to healthy bleeding bone. The defect is templated, and the allograft is harvested and prepared. The allograft is securely fixed using cannulated cancellous screws. The patient undergoes a postoperative rehabilitation protocol. Results: There have been several case series following allograft reconstruction for locked posterior dislocations that have demonstrated good results. Riff et al found favorable results in his series of 20 patients with isolated humeral head lesions, with significant improvement in patient-outcome measures. There are several potential complications though. A systematic review by Saltzman et al found allograft resorption to occur in 36% and glenohumeral arthritic changes to occur in 35% with frozen allografts. These rates appear to be improved with fresh allografts. Discussion/Conclusion: In conclusion, osteochondral allograft is an effective surgical treatment for large Hill-Sachs defects in chronic locked posterior dislocations.